Risk of upper gastrointestinal complications in a cohort of users of nimesulide and other nonsteroidal anti‐inflammatory drugs in Friuli Venezia Giulia, Italy12. (11th December 2012) - Castellsague, Jordi; Pisa, Federica; Rosolen, Valentina; Drigo, Daniela; Riera‐Guardia, Nuria; Giangreco, Manuela; Clagnan, Elena; Tosolini, Francesca; Zanier, Loris; Barbone, Fabio; Perez‐Gutthann, Susana
ABSTRACT: Purpose: Information on the risk of upper gastrointestinal complications (UGIC) in users of nimesulide, the most used nonsteroidal anti‐inflammatory drug (NSAID) in Italy, is scarce. In the context of the European regulatory review on nimesulide, we estimated and compared the risk associated with nimesulide and other individual NSAIDs with the risk in nonusers. Methods: We used 2001–2008 data from regional health databases in Friuli Venezia Giulia (FVG), Italy, to conduct a cohort and nested case–control study of users of NSAIDs. Cases were identified by specific and nonspecific hospital discharge diagnoses in primary and secondary position and validated through hospital records. Ten controls per case were selected using density‐based sampling from the cohort. Conditional logistic regression was used to estimate adjusted relative risks (RRs) and 95% confidence intervals (CIs). Results: The cohort included 588 827 NSAIDs users and 3031 UGIC cases. Nonspecific codes contributed to 23% of cases and secondary codes to 5%. Among current users, IR per 1000 person‐years decreased from 4.45 cases in 2001 to 2.21 cases in 2008. The RR (95%CI) for current use of NSAIDs was 3.28 (2.86, 3.76). RR was <2 for rofecoxib, celecoxib, and nimesulide; 2 to <5 for naproxen, ibuprofen, diclofenac, etoricoxib, and meloxicam; and ≥5 for ketoprofen, piroxicam, and ketorolac. Conclusions: IRs of UGIC in FVG decreased about 50% between 2001 and 2008. Nimesulide was in the low–medium range of RR. A complete ascertainment of UGIC cases in databases may require validation of nonspecific codes, secondary codes, and additional codes such as peritonitis and acute posthemorrhagic anemia. Copyright © 2012 John Wiley & Sons, Ltd.